2008
DOI: 10.2116/analsci.24.1251
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Behavior of Divalent Metal Cations in Ionic Liquid Chelate Extraction Systems Using 1-Alkyl-3-methylimidazolium Bis(trifluoromethanesulfonyl)imides and Thenoyltrifluoroacetone

Abstract: The extraction behavior of several divalent metal cations (M 2+ ) in ionic liquid chelate extraction systems was investigated using several 1-alkyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquids ([Rmim][Tf2N]) as extraction solvent and thenoyltrifluoroacetone (Htta) as extractant. The behavior was compared with that using less hydrophobic 1-alkyl-3-methylimidazolium hexafluorophosphates ([Rmim][PF6]). The extracted species in the [Rmim][Tf2N] systems were neutral M(tta)2 for M = Cu a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…For example, several divalent transition metals 20,24 and trivalent lanthanoids 25 were extracted into ILs with 2-thenoyltrifluoroacetone (Htta) as monoanionic complexes. Moreover, the ion-exchange abilities may affect the distribution behavior of extraction reagents between the two phases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several divalent transition metals 20,24 and trivalent lanthanoids 25 were extracted into ILs with 2-thenoyltrifluoroacetone (Htta) as monoanionic complexes. Moreover, the ion-exchange abilities may affect the distribution behavior of extraction reagents between the two phases.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Because ILs can also act as liquid ion exchangers, not only neutral but also charged complexes are extractable into the IL phase by ion exchange with the cationic or anionic constituent of the ILs. [10][11][12][13] Thus, the extractability and separability of metal ions in the IL extraction system are expected to differ from those of the usual organic solvent systems. 14,15 Recently, the present authors have reported on the synergistic ionic-liquid extraction of lanthanoids(III) (Ln(III)) with 2-thenoyltrifluoroacetone (Htta) as an acidic chelating extractant and several neutral ligands in 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([C4mim][Tf2N]).…”
mentioning
confidence: 99%
“…In literature, Cu(II) extraction in ionic liquids by differrent chelating agents has been already reported [10,11]. In our previous study [12], concerning the extraction of Hg(II) ions in ionic liquids in absence of chelating agent, the key role of both working temperature and ionic liquid hydrophobicity has been pointed out.…”
Section: Cu(ii) Extraction In Ionic Liquidsmentioning
confidence: 95%